2019
DOI: 10.2478/acve-2019-0039
|View full text |Cite
|
Sign up to set email alerts
|

Penile Foreign Bodies in Dogs: A Retrospective Study

Abstract: Hematuria, or preputial hemorrhagic discharge, is an extremely common clinical sign; it can be associated with a wide range of diseases, including, even if only rarely, penile foreign bodies. The aim of this retrospective study was to describe the diagnosis and therapy involving migration from the preputial ostium or penile urethra of a foreign body (awn grass) embedded in the connective tissue surrounding the penis, or in deeper inguinal tissues, in dogs with hematuria or preputial hemorrhagic discharge. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In five dogs, the vegetal foreign bodies were visualized in the balano-preputial sulcus, embedded in the subcutaneous tissue; in another dog, a grass awn was detected in the inguinal region. The authors confirmed the usefulness of US for localization and removal of migrating grass awns in all the patients [47]. In 2020, Marchesi et al described ultrasonographic findings of a migrating grass awn in canine prostatic parenchyma and subsequent echo-guided removal of the foreign body [49].…”
Section: Genitourinary Tract Migrationmentioning
confidence: 66%
See 2 more Smart Citations
“…In five dogs, the vegetal foreign bodies were visualized in the balano-preputial sulcus, embedded in the subcutaneous tissue; in another dog, a grass awn was detected in the inguinal region. The authors confirmed the usefulness of US for localization and removal of migrating grass awns in all the patients [47]. In 2020, Marchesi et al described ultrasonographic findings of a migrating grass awn in canine prostatic parenchyma and subsequent echo-guided removal of the foreign body [49].…”
Section: Genitourinary Tract Migrationmentioning
confidence: 66%
“…Del Signore et al reported the case of a dog with a vegetal foreign body in the preputium, which was removed with Hartmann US-guided technique [ 48 ]. Bergamini et al published a retrospective study including six dogs with hematuria and preputial discharge secondary to grass awn migration [ 47 ]. In five dogs, the vegetal foreign bodies were visualized in the balano-preputial sulcus, embedded in the subcutaneous tissue; in another dog, a grass awn was detected in the inguinal region.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Urinary bladder or urethral foreign bodies have been rarely reported in the veterinary literature. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Urinary bladder foreign bodies have been related to a penetrating gunshot, 1 migration from the gastrointestinal tract, urogenital tract, or percutaneous migration from the skin. [2][3][4][5][6] Iatrogenic causes due to a retained urinary catheter fragment, 7 string from a feed sack used to ligate spermatic cord, 14 and laser fiber fractured during lithotripsy 8 have also been reported.…”
Section: Discussionmentioning
confidence: 99%